Neural tube defects: contemporary outcome data in a setting in which pregnancy termination is not locally available. (7th June 2011) - Unterscheider, J; Kent, E; Burke, N; Wiig, U; Breathnach, F; Malone, F
Abstract : Ireland continues to experience a high incidence of neural tube defects (NTD). Knowledge about the natural history of this condition is limited as pregnancy termination is practiced in most countries. We aimed to describe perinatal outcomes of pregnancies complicated by fetal NTDs in a setting in which pregnancy termination is not locally available. We conducted a retrospective cohort study over a 6-year period in a tertiary referral center in Dublin (2005–2010). Only singleton gestations with confirmed normal karyotype were included for analysis. During the study period 1742 women attended a specialist clinic to confirm and manage fetal abnormalities. NTDs accounted for 4.5% of consultations. We identified 78 consecutive cases of NTD; these comprised 29 meningomyeloceles (37%), 11 encephaloceles (14%) and 38 cases of anencephaly (49%). The majority of pregnancies affected by anencephaly were terminated (71%). Of the 11 cases of anencephaly in which expectant management was chosen, 7 (64%) infants were liveborn. Of the 39 non-lethal NTDs, 15 patients (38%) terminated their pregnancy. Of the 23 ongoing pregnancies with available outcome data, four fetuses with encephaloceles (19%) had an intrauterine fetal demise at a mean gestational age of 24+2 weeks. Of the 19 liveborn infants, 15 (79%) were delivered by caesarean section. There were 3 neonatal deaths (16%). 16 infants underwent meningomyelocele closure ± ventriculoperitoneal shunting. 14/16 (88%) were alive at follow-up (2 months to 6 years). The above natural history outcome data provides useful information for health professionals charged with prenatal counselling for NTD.